Impact of single versus dual arterial supply on perfusion and function in finger replantation after complex hand injuries - Martynas Tamulevicius; Malte David Steinbach; Florian Bucher; Nadjib Dastagir; Doha Obed; Peter M. Vogt; Khaled Dastagir (Scientific Reports)
Abstract Finger amputations following complex hand injuries (CHI) pose a significant challenge in hand surgery due to severe tissue trauma and neurovascular damage, necessitating precise arterial repair. While restoring arterial perfusion is critical, it remains unclear whether reconstructing both proper palmar digital arteries is required for optimal outcomes. This study evaluates whether restoring one or both arteries in finger replantation after complex injuries impacts perfusion and overall outcomes. In this retrospective, cross-sectional, follow-up study, we investigated patients with finger amputations following CHI admitted to the high-volume regional hand trauma center between January 2013 and December 2020. Perfusion has been assessed using FLIR thermal imaging and laser speckle contrast analysis. Functional outcomes and quality of life scores were measured using standardized questionnaires. Sensory assessments, along with pain and grip strength measurements were also conducted. A total of 31 patients were included in the study. Thermal imaging showed a significantly higher finger surface temperature in patients with two-artery reconstruction. Laser speckle contrast analysis confirmed better perfusion, though not statistically significant. Functional and quality-of-life scores were similar across groups, except for significantly improved temperature sensation in the two-artery group. In conclusion, reconstructing both arteries in finger replantation following CHI isn’t essential for good outcomes if one artery provides adequate perfusion, but dual reconstruction may improve perfusion and temperature sensation.